Effectiveness of behaviour change communication for preventing tobacco use among high school children in rural area, Bengaluru - Rajeshwari, Swetha; S., Hemavarneshwari; P., Sathyanarayana (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescents in high school are vulnerable to various health risk behaviors. One of it is tobacco use which is the leading cause of death and disease worldwide today. Educational programs applied in schools can have immense potential in promoting healthy behaviours and help them to refrain from risky behaviours among school going adolescents. The objectives of the study were to assess the prevalence of tobacco use among high school students in the rural field practice area of Vydehi Institute of Medical Sciences and Research Centre, Bengaluru and to evaluate the effectiveness of behavior change communication using life skills education on tobacco use initiation and cessation of use among high school children Methods: An interventional study was conducted in a randomly selected rural high school. A total of 454 students studying in 8th 9th and 10th standard participated in the study. Pretested semi structured questionnaire was used to collect data. Intervention was given in the form of life skills education with interactive sessions involving debates, group discussions, role plays, situational analysis on prevention of tobacco use. Follow up was done at intervals of 1 month, 3months, and 6 months to assess the change in tobacco use prevalence using a questionnaire. Results: Over all, prevalence of tobacco use was 69 (15.2%) with 50 (11%) being male and 19(4.2%) female students. Prevalence of tobacco use reduced from 69 (15.2%) during pre-intervention to 58 (12.9%), 39 (8.7%), and 33 (7.3%) by the end of one month, three months and six months respectively after the intervention. Conclusions: There is lack of awareness regarding dog bite and its management among the rural population.